Empowered or constrained? Gender narratives in Cyberpunk-style microfilm advertisements - Chunfa Zhou; Beile Jin (Humanities & Social Sciences Communications)
Abstract This study examines the portrayal of gender in Cyberpunk-style microfilm advertising (CMA), a genre that blends futuristic technology with dystopian elements. By employing qualitative content analysis grounded in theories of gender performativity and media representation, this research examines how these advertisements construct gender images and their impact on societal gender norms. The analysis reveals that while CMA presents innovative gender representation, it also perpetuates existing stereotypes, particularly with regard to professional roles and emotional dynamics. The findings underscore the dual role of media in both challenging and reinforcing gender stereotypes and highlight the need for a more balanced portrayal of gender. This study contributes to the discourse on gender representation in media, offers insights into the unique intersection of Cyberpunk aesthetics and advertising, and calls for further research to explore the long-term effects of these representations on societal norms.